The credit channel of monetary policy: Case of Austria - Elizaveta Krylova (Institute for Advanced Studies (IHS), 2002)
The legal environment, the structure of the financial system as well as the concentration of corporate ownership and the development of the capital market suggest for Austria a high effectiveness of the monetary policy with a strong impact of the lending channel. This supposition was verified combining three supplementary empirical methods: Granger causality between the velocities of money and loans and the real output; impulse-response functions for VECs with the subsequently opened/closed money/credit channels; the predictive power of money and loan variables for a production forecast. Both various types of loans and the total volume of credits for separate banking groups were examined. The Austrian output showed to be highly sensitive to monetary policy innovations; both the money and the credit channel were significant. The dependence of Austrian firms on credits rather than on other financial resources was more pronounced for credits in domestic currency, mortgage loans and municipal notes.
Keywords: E52; C50; C53; 330; monetary transmission mechanism; credit channel; Austria; Transmissionsmechanismus; Kreditkanal; Kredit; Schätzung; Österreich